The Cambridge handbook of natural law and human rights - Angier, Tom 1970-; Benson, Iain T. 1955-; Retter, Mark ca. 20./21. Jh (Cambridge University Press, 2023)
This Handbook provides an intellectually rigorous and accessible overview of the relationship between natural law and human rights. It fills a crucial gap in the literature with leading scholarship on the importance of natural law as a philosophical foundation for human rights and its significance for contemporary debates. The themes covered include: the role of natural law thought in the history of human rights; human rights scepticism; the different notions of 'subjective right'; the various foundations for human rights within natural law ethics; the relationship between natural law and human rights in religious traditions; the idea of human dignity; the relation between human rights, political community and law; human rights interpretation; and tensions between human rights law and natural law ethics. This Handbook is an ideal introduction to natural law perspectives on human rights, while also offering a concise summary of scholarly developments in the field